Criteria for the Development of Methodological Competence of Future Teachers of Technology - Valijonovich, Nosirov Nodirbek (Researchparks Publishing, 2023)
In the course of education, future teachers are given ample opportunities to develop methodical competence. Effective use of available opportunities serves to achieve the expected results in this regard. The fact that science teachers have criteria for evaluating the level of development of relevant qualities ensures the consistency and effectiveness of practical actions to develop methodical competence in future students. The article talks about the criteria for evaluating the development of the methodological competence of future students.